Detection of Ground Water Availability at Buhias Island, Sitaro Regency - Tamod, Zetly E; Polii, Bobby; Sikome, Ruth Maria (Forum Geografi, 2016)
The study aims to detect ground water availability at Buhias Island, Siau Timur Selatan District, Sitaro Regency. The research method used the survey method by geoelectrical instrument based on subsurface rock resistivity as a geophysical exploration results with geoelectrical method of Wenner-Schlumberger configuration. Resistivity geoelectrical method is done by injecting a flow into the earth surface, then it is measured the potential difference. This study consists of 4 tracks in which each track is made the stretch model of soil layer on subsurface of ground.Â  Then, the exploration results were processed using software RES2DINV to look at the data of soil layer based on the value of resistivity (2D). Interpretation result of the track 1 to 4 concluded that there is a layer of ground water. State of dominant ground water contains the saline (brackish). Location of trajectory in the basin to the lowland areas is mostly mangrove swamp vegetation. That location is the junction between the results of the runoff of rainfall water that falls down from the hills with sea water. Bedrock as a constituent of rock layer formed from marine sediments that carry minerals salts.